Reconfigurable Topography for Rapid Solution Processing of Transparent Conductors. (20th October 2013) - Wu, Haosheng; Menon, Monisha; Gates, Evan; Balasubramanian, Aditya; Bettinger, Christopher J.
<x xml:space="preserve">Abstract</x> Cost‐effective materials for transparent conducting electrodes are essential for many devices used in clean energy production and consumer electronics. Here we report a technique for non‐lithographic patterning of silver nanowires on flexible substrates from solution via microcontact transfer printing using donor substrates with reconfigurable topography. This approach is a highly scalable fabrication strategy for high performance transparent conductors. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>